A comparison of intramedullary nailing versus plating in AO type 15.2B and 15.2C clavicle fractures: a prospective study - Jain, Nikhil; Sharma, Pranshu; Jain, Ayush (International Journal of Research in Orthopaedics, 2025)
Background: Midshaft clavicle fractures, particularly AO types 15B and 15C, are common orthopedic injuries. Surgical management is preferred in displaced fractures due to complications associated with conservative treatment. This study compares intramedullary fixation using titanium elastic nailing system (TENS) with conventional plating. Methods: A prospective cohort study was conducted on 80 patients aged 15-70 years with AO 15B and 15C clavicle fractures. Patients were randomized into two groups: one treated with TENS and the other with plating. Surgical, radiological, and functional outcomes were evaluated at 1, 3, and 6 months postoperatively using Constant-Murley and DASH scores, union time, and complications. Results: TENS group had significantly shorter union time (7.4 weeks vs. 8.9 weeks, p=10.024), smaller incision size, and shorter hospital stay. Functional scores were superior in the TENS group. TENS group had significantly shorter union time (p=0.024), smaller incision size, and shorter hospital stay. Implant prominence was more common with TENS, but plating had higher rates of infection, non-union, and implant failure. Conclusions: TENS provides superior functional recovery, better cosmetic results, and fewer complications in AO 15B and 15C clavicle fractures. It is a cost-effective and efficient alternative to plating, especially in resource-limited settings. However, plating may offer more stable fixation in complex fracture patterns.